Religion and development: Tracing the trajectories of an evolving sub-discipline. (July 2019) - Bompani, Barbara
Religion and development (RaD) has emerged as a new academic sub-discipline since the turn of the 21st century, following decades of secular assumptions and attitudes dominating development studies, and international development more broadly. In 2019, there was a little doubt that religion has been incorporated into development studies and it is therefore timely to re-appraise RaD. Recent scholarship suggests that RaD increasingly informs, engages with and influences development studies and development practice—providing rich empirical material, broader disciplinary engagement and deeper analytical insight. Drawing on a survey of almost—mainly English language—700 publications, this article traces the emergence and establishment of RaD. The article traces the emergence of the field (2000–10) and then its subsequent more critical engagement with development studies (between 2011 and 2018). The article concludes by identifying five emerging contemporary research themes within RaD and future research opportunities.